Turning off the taps: the termination of state sponsorship - Karlén, Niklas (Terrorism and political violence, 2019)
Why do some states terminate their sponsorship of rebel movements while others are persistent in their provision of support? In the past, most research on external support to insurgents has focused on why states choose to sponsor rebel groups and particularly how this affects conflict duration. However, we know little about the termination of such support. This is surprising given that support has been shown to make armed conflicts more intractable and tremendous efforts are made in condemning and sanctioning such behavior. This study constitutes the first large-N analysis of support termination, employing survival analysis on global data of state support to rebel movements between 1975–2009. Surprisingly, the findings indicate that only some of the factors that explain support provision can offer insights into its termination. In particular, support is more likely to be terminated when no ethnic kinship bonds exist between the rebel movement and the government of the supporting state. Many decisions to withdraw support also seem to coincide with the transition from the Cold War. Threats and sanctions from other states appear largely ineffective. The study contributes to our understanding of the international dimensions of civil war and the role and motives of third parties.